VD_FINDINFO Arrêt / 2024 / 679 vom 26. August 2024 - VD Tribunal cantonal (2024)
ERREUR DE CALCUL, ADMISSION DE LA DEMANDE, DÉCISION DE COTISATIONS | 1a al. 1 LAVS, 10 al. 1 LAVS, 3 al. 1 LAVS, 28 RAVS, 29 RAVS